Tūtira mai! Reporting a Tiriti o Waitangi settlement ceremony for public radio through a Māori lens - Middleton, Atakohu (Te Kaharoa, 2022)
Radio New Zealand is a Government-owned public broadcaster in Aotearoa New Zealand. Its news channel, RNZ National, has among its reporting team Māori journalists who report in English on issues of significance to Māori for a national audience that is predominantly non-Māori. This case study documents the activities of a bilingual Māori RNZ National reporter as she covers a Tiriti o Waitangi settlement between the Crown and a collective of East Coast iwi (tribes). It traces how the reporter balances tikanga, or Māori cultural norms, with journalistic demands as she produces news stories for the internet and radio and images for Twitter. The news content is presented and analysed through the lens of the Anglo-American news values in operation in Aotearoa New Zealand, demonstrating how Māori history, culture and aspiration are centred within these. This paper assumes some understanding of news values and journalistic practice and process.